FACTORS ASSOCIATED WITH THE INCIDENCE OF HYPERTENSION IN GAMPONG BAROH VILLAGE, SETIA BAKTI DISTRICT, ACEH JAYA REGENCY - Firdaus , Muhammad; Lensoni, Lensoni (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
One of the most common non-communicable diseases experienced by people in Indonesia is hypertension. Hypertension is a disease in which the blood pressure in the blood vessels increases chronically. This can happen because the heart works harder to pump blood to fulfill the body's need for oxygen and nutrients. If left untreated, this disease can affect the function of other organs, especially important organs such as the heart and kidneys. This study is quantitative study with cross-sectional or cross-sectional approach and also observational. From the results of bivariate analysis, the relationship between history of hypertension and the incidence of hypertension obtained a p value of 0.000 with an α value of 0.05, p≤α means that there is a relationship between hypertension history factors. The relationship between gender and the incidence of hypertension obtained a p value of 0.166 with an α value of 0.05, p≥α means there is no relationship. The bivariate relationship between physical activity and the incidence of hypertension obtained p value of 0.028 with an α value of 0.05, p≤α means there is relationship. Based on the study of factors associated with the incidence of hypertension in Gampong Baroh Village, Setia Bakti Subdistric, it can be concluded that there is relationship between history of hypertension, physical activity and salt consumption with the incidence of hypertension and there is no relationship between gender, age and smoking with the incidence of hypertension.